The Influence of Tax Sanctions, Taxpayer Awareness, and Tax Service Quality on Individual Taxpayer SPT Reporting Compliance - Amalia, Erma Vernanda; Hernawati, Retno Indah; Durya, Ngurah Pandji Mertha Agung; Isthika, Wikan (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The aim of the research is to determine the effect of tax sanctions, taxpayer awareness, and tax service quality on individual taxpayer tax return reporting compliance (Study on employees of Bank BTN Syariah KCS Semarang). The population of this study consisted of 126 respondents and used a saturated sample. The data collection technique uses print media in the form of a questionnaire distributed to employees of Bank BTN Syariah KCS Semarang. Data analysis uses descriptive statistical tests, validity & reliability tests, classical assumption tests, multiple linear regression tests, model tests and hypothesis tests. The results of the research prove that tax sanctions and the quality of tax services influence taxpayer compliance, while taxpayer awareness does not influence taxpayer compliance.